Research on Regional Spatial Emergency Communication System - Wei He; Renchao Xie; Tao Huang; Renfeng Liu (Dianxin kexue)
Regional spatial emergency communication system not only has a low delay,large capacity advantages,but also has fast system construction and easy maintenance properties,which has a broad application prospects.The feasibility of regional space emergency communication system was discussed,then the architecture of regional spatial emergency communication system was designed,and the application scenario of regional spatial emergency communication used in power emergency communication was discussed.Finally,the key technical issues based on this system architecture were discussed,which could provide a guideline to study the regional spatial power emergency communication.